EVALUATION THE DEGREE OF ROOT RESORPTION CAUSED BY CANINE TOMOGRAPHIC IMPACTED - Arakaki-Chinen, Naomi (2016)
Objective: the proposal of this study was to examine the degree of root resorption in parts adjacent to impacted maxillary canines, bymeans of a cone-beam computerized tomographic evaluation, which has proven to be a reliable and accurate method to assess thistype of complications. Materials and methods: this study was an evaluation of 1265 ct, which obtained a sample of 72 ct with caninesimpacted maxillary, 36 men and 36 women, ranging from 13 to 43 years old. The variable studied was reabsorption of the adjacent part:the classification of levander and malmgren was used to assess the degree of root resorption. Results: it was observed that 49% hadgrade 0 reabsorption, followed by 19% grade 3 reabsorption. No statistically significant difference was found according to sex p = 0.47.This study found a greater number of patients younger than 18 years presenting root resorption of incisor side (63%) compared topatients older than 18 years (38%).